PROFESSORIAL LECTURE: UTILISING AUDITORY EVOKED POTENTIALS FOR INTERVENTIONS IN CHILDREN WITH AUTISM - DZULKARNAIN, AHMAD AIDIL ARAFAT (International Journal of Allied Health Sciences, 2025)
Auditory evoked potential (AEP) is a vital tool for audiologists worldwide. It is an objective measure of auditory function, capable of estimating an individual’s hearing status and diagnosing disorders within the central auditory nervous system. The most common applications of AEP include estimating hearing thresholds, hearing screenings, and neurodiagnostic evaluations. Less commonly, AEP is used to assess the effectiveness of interventions, predict outcomes of audiological treatments, or forecast the likelihood of certain disorders.